Analysis of Emotional Quotient (EQ) Ability in U-17 Athletes of Terang Bangsa Football School - Aminullah, Rizky (UNIB Press, 2025)
This study aims to analyze the Emotional Quotient (EQ) abilities of athletes from the Terang Bangsa U-17 Football School (SSB), focusing on three main aspects: emotional stability, emotional strength, and emotional satisfaction. These components play a crucial role in supporting athletes’ performance under competitive pressure. A quantitative descriptive method was used, involving 26 athletes selected through purposive sampling. The research instrument was an EQ test consisting of 75 items with a completion time of 45 minutes. The results showed that 53.8% of athletes were categorized as highly stable in terms of emotional stability, 65.4% demonstrated strong emotional strength, and 80.8% were highly satisfied emotionally. These findings indicate that, in general, the athletes of SSB Terang Bangsa U-17 possess a good level of EQ, contributing positively to their motivation, emotional resilience, and psychological well-being. However, the study highlights the need for continuous mental training, especially for athletes who fall into the lower categories in one or more EQ dimensions. In conclusion, the development of emotional intelligence is an essential component of psychological coaching in sports.